Uncoordinated Cooperative Multihop Forwarding in 2D Highly Dynamic Networks. (16th August 2015) - Zhang, Xuefei; Tao, Xiaofeng; Cui, Qimei
This paper investigates cooperative forwarding in two-dimensional highly dynamic wireless networks. Unlike traditional coordinated cooperative forwarding schemes that require a large amount of neighborhood discovery and coordination information to be exchanged before making the forwarding decision, this paper proposes an uncoordinated cooperative forwarding scheme where each node determines whether or not to forward a received packet independently based on a forwarding probability determined by its own location, the locations of the destination, and the transmitter from which it receives the packet, without the costly or even impractical neighbor discovery and coordination process. Analytical results are derived for the successful transmission probability and the expected number of forwarding nodes involved in the cooperative forwarding process. On that basis, discussions are presented on the optimal forwarding probability design that meets a predesignated successful transmission probability target using minimum number of forwarding nodes. Simulations are conducted to evaluate the performance of the proposed scheme.